Educação escolar e mediação: impactos das tecnologias digitais no processo de formação - Santos, Elaine Cristina Moraes [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Considering the diffusion of digital technologies in the contemporary society, as well as its expansion in the school environment, this study has the mediation process as an analysis category, with the objective of problematizing what kind of knowledge those digital resources are able to promote. When scrutinizing the role of school practice in the society, as well as the ideological mechanisms that hide the main purpose of technological phenomena, this study contains the following hypothesis: the way in which digital technologies are included in current educational policies preclude an emancipatory educational mediation, generating evidently faced impact on the practice of the students and the human formation. This is a theoretical and bibliographic research, guided by a dialectic perspective, whose approach goes toward to the German Critical Theory of society, particularly from the reflections of Theodor Adorno, Max Horkheimer, Herbert Marcuse and Christoph Türcke

Considerando a difusão das tecnologias digitais na sociedade contemporânea, assim como, sua expansão no ambiente escolar, este estudo tem como categoria de análise, o processo de mediação, como o caminho para problematizar, que tipo de conhecimento estes recursos digitais são capazes de promover. Ao se perscrutar o papel da prática escolar na sociedade, bem como sobre os mecanismos ideológicos que ocultam a principal finalidade dos fenômenos tecnológicos, este estudo contém a seguinte hipótese: a forma com que as tecnologias digitais estão inseridas nas atuais políticas educacionais inviabiliza uma mediação pedagógica emancipadora, gerando impactos evidentemente enfrentados na prática escolar e na formação humana. Trata-se de uma pesquisa de cunho teórico-bibliográfico, de perspectiva dialética, cuja abordagem está voltada para a Teoria Crítica da sociedade, particularmente a partir das reflexões de Theodor Adorno, Max Horkheimer, Herbert Marcuse e Christoph Türcke
Keywords: Adorno, Theodor W. 1903-1969 Critica e interpretação; Horkheimer, Max 1895-1973 Crítica e interpretação; Marcuse, Herbert 1898-1979 Crítica e interpretação; Educação; Tecnologias de informação e comunicação; Education